CFD Simulation of Pipe Joints Using SimScale: Analysis of the Effect of Different Inlet Velocities on Water Fluid Flow - Hasbiyati, Haning; Aulina, Audha Fitrah (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of variations in inlet velocity on fluid flow patterns at tee-junction pipe connections using numerical simulations based on Computational Fluid Dynamics (CFD). The SimScale platform was used because it supports cloud-based processing and integration with OpenFOAM solvers. The tee connection model is designed in three dimensions, with the main and branch pipe dimensions each having a diameter of 100 mm. The merging process uses the parametric hexagonal method and local refinement in the joint area to accurately capture turbulent phenomena. Simulations were performed under incompressible and isothermal flow conditions with a standard k–ε turbulence model, using water fluid and the SIMPLE algorithm. The inlet velocity consists of 2 variations A (VI = 1 m/s, V2 = -1 m/s) and variation B (V1 = -1.5 m/s, V2 = -3 m/s). Simulation results show that increasing the inlet velocity results in a more turbulent flow, characterized by an increase in the turbulent kinematic viscosity, specific dissipation rate, and turbulent kinetic energy. Conversely, low velocities indicate higher pressure accumulation due to flow resistance. These findings indicate that inlet velocity variations significantly affect flow characteristics, requiring attention in system design to maintain long-term operational efficiency and reliability.